Indoor broadcasting using visible free space optic over broadband powerline communication - Alavi Ghahferokhi, Sayed Ehsan (2012)
Visible Free Space Optic (VFSO) is a new and attractive technology, which employs visible light generated by white light emitting diode (LED) for optical wireless communications. In addition, it is possible to use ubiquitous powerline cables as a communication medium among other fixed network equipments which is powerline communication (PLC) technology. An integrated system of VFSO and PLC uses existing powerline cables and white LEDs as a communication channel hence it has the advantage of low operating cost and provides easy data transmission. The current integrated system encounters some problems due to PLC multipath, noise, and no practical modeling for white LEDs, which degrades significantly the performance of the whole system. Therefore, this study presents the optimum orthogonal frequency division multiplexing (OFDM) modulating signal power, proper DC biasing point, and LED dynamic range to solve system degradation. Moreover, a practical LED model is also presented, and the performance of the integrated system in terms of OFDM signal power versus bit error rate in the presence of broadband PLC impulsive noise, multipath issue, and additive white Gaussian noise optical channel is studied. Based on indoor applications, the primary purpose for VFSO link is the general lighting designation with the standard brightness level and the secondary purpose is for data transmission. Therefore, to have a high quality VFSO link besides ensuring sufficient horizontal brightness of the place, high data rate of optical communication links with low bit error rate are also achieved. The radiometric parameters of white LEDs using simulation and experiment are reported. Optimum 15dBm OFDM signal power, (3.2V, 350mA) biasing point, and 1Vp-p dynamic range for white LED has the data rate more than 28Mbits/second with the bit error rates lower than 610? . Moreover, at least 400lx of indoor lighting was also fulfilled. So, the new integrated system is considered as a good alternative for other indoor wireless system counterparts.